Peripheral haematology of Puntius filamentous (Valenciennes) in relation to sex, maturity, standard length and seasons (Pisces : Cyprinidae) - Vijayakumari, K.N.; Murali, D. (Indian Journal of Fisheries, 2012)
Peripheral haematological parameters such as total erythrocyte, leucocyte and thrombocyte counts (TEC, TLC, TTC),haemoglobin content (Hb), haematocrit (Ht), erythrocyte sedimentation rate (ESR), RBC/WBC ratio, mean corpuscularvolume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) ofPuntius filamentosus in relation to sex, maturity stages, standard length of the fish and seasons were analysed. The results ofthe present study shows that peripheral haematological make-up is not much affected by the sex of the fish. However, mostof the haematological parameters (TEC, TLC, TTC, Hb and Ht) registered higher mean values in males than in females.Gonad maturity has only little influence on the peripheral haematological make-up. But there was a general tendency fordecrease in the mean values of TEC, TTC, Hb and Ht in fish at maturity stage IV. Simple linear correlation analysis (r)revealed that TTC (p